Development of an Electric Vehicle Dashboard Monitoring System Using Microcontroller - Abozaed, Mohammed E. Salem (2000)
A microcontroller is a complete microcomputer on a chip that integrates a CPU with memory and various peripherals such as analog-to-digital converters (AID), serial communication units etc. Microcontrollers are designed to be embedded within event-driven control applications and generally have all necessary peripherals integrated onto the same piece of silicon. An Intelligent Energy Management System (IEMS) is a microcontroller based system which is used in an electric vehicle to monitor and control the various parts of the vehicle such as the motor and motor drives, the current and voltage of the battery packs, dashboard, pedals and other subsystems. This aids the driver to achieve optimal driving conditions from the vehicle. In tropical countries the temperature is very high especially during the day. As a result, when the vehicles are parked in an open space the temperature in the vehicle rises and this could lead to many problems. The objective of this project was to develop an Automatic Fan Controlling System (AFCS), which may be used to control the temperature of the electrical vehicle cabin to counter any potential problems. This new proposed system is one of the many systems that may be made available to the user via the IEMS. This project also looked into the development of the battery pack voltage level monitoring system for electric vehicles. The MC68HC11 evaluation board (EVB) NMIX-0020, which uses a Motorola F68HCll microcontroller for its CPU, is used to monitor and control both of the systems mentioned above. The development work carried out for the automatic fan controlling system and the battery pack voltage level monitoring system include the design, construct and testing of the system. The automatic fan controlling system consists of a temperature sensor (AD590), a current-to-voltage converter, digital relay and a microcontroller. The battery pack voltage level monitoring system comprises of a voltage divider, a digital display and a microcontroller. Simulation and experimental results are also included and discussed in detail. Based on these results, the systems mentioned above have been successfully developed. The systems can be extended for high temperature controlling and high voltage monitoring by changing some parameters in both systems.